2021
DOI: 10.1016/j.sjbs.2021.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Determination of antimicrobial and phytochemical compounds of Jatropha curcas plant

Abstract: The aim of this study was to explore the effectiveness of different parts of J. curcas plant against some selected human pathogens as antimicrobial agent which are known to cause diseases and to check antioxidant and phytochemicals from different plant sections of J. curcas . Plant extracts were analyzed by quantification of antimicrobial and phytochemical compounds. This study reveals that 20% ethanol stem extract of J. curcas showed maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Both samples of IG and PK were analyzed for the comparative analysis of the presence of phytochemicals such as Alkaloids, Saponin, Tannin, Flavonoids, Phytosterol, Phenol, Anthraquinone, Cardiac glycosides, Carbohydrates, Terpenoids and Steroids, through precipitation and coloration reactions methods, as reported in our earlier work. 17…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both samples of IG and PK were analyzed for the comparative analysis of the presence of phytochemicals such as Alkaloids, Saponin, Tannin, Flavonoids, Phytosterol, Phenol, Anthraquinone, Cardiac glycosides, Carbohydrates, Terpenoids and Steroids, through precipitation and coloration reactions methods, as reported in our earlier work. 17…”
Section: Methodsmentioning
confidence: 99%
“…26 A small portion of pre-cultured microorganisms through the inoculation loop was transferred into prepared 10 mL Luria Bertani (LB) media and stored in an incubator at 37 ° C for 24 h as previously described in our work. 17,27 The turbidity of LB media was adjusted using 0.5 McFarland standard at a concentration of 10 8 Cells/mL. The fungal specimens of pre-cultured Aspergillus niger and Penicillium crysogenum in Petri-dishes of potatoes dextrose agar were also obtained from IBGE.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have indicated the presence of flavonoids, alkaloids, coumarins and lignins in J. gossypiifolia and J. curcas [ 39 , 40 ]. Other studies have shown the presence of flavonoids, polyphenols, saponins and condensed tannins in the extract of J. curcas leaves [ 41 ], and flavonoids and polyphenols in the ethyl acetate fraction of leaves and roots of J. macranta [ 42 ]. Other authors have also reported similar results [ 43 , 44 , 45 , 46 ], indicating that they align with the results found here.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, research has been conducted to determine the concentration of secondary metabolites in plants of the genus Jatropha . Concentrations of phenols in the range of 400 to 150 μg·mL −1 , flavonoids of 6 to 2 μg·mL −1 and tannins of 35 to 10 μg·mL −1 were identified in the aqueous, ethanolic, methanolic and ketone extracts of the seeds, roots, leaves, flowers and bark of J. curcas [ 41 ]. In studies by Fröhlich et al [ 47 ], the total concentration of phenols, flavonoids and tannins in the crude extract and the dichloromethane, acetate and butanolic fractions of the roots of J. isabellei was determined.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the diameter of each disc's bacterial inhibition zone was used to measure its antimicrobial power. Each test was completed in triplicate, and the average diameter of the inhibitory zone was measured [10][11][12].…”
Section: Screening For Antimicrobial Activitymentioning
confidence: 99%